Penyuluhan Asuhan Kebidanan Pada Wanita Lansia Tentang Pencegahan Infeksi Saluran Kemih Dan Osteoporosis - Cakrawati Cakrawati; Sastrika Handayani Marpaung (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The increasing number of elderly women leads to various health problems, particularly urinary tract infections (UTIs) and osteoporosis, which commonly occur due to physiological and hormonal changes. The lack of knowledge among elderly women regarding disease prevention contributes to the high incidence of UTIs and reduced quality of life. This community service activity aimed to improve the knowledge and awareness of elderly women about the prevention of UTIs and osteoporosis through midwifery health education at the Community Health Center X. The implementation methods included interactive lectures, group discussions, light exercise demonstrations, and distribution of educational leaflets. A total of 40 elderly women aged 55–70 years participated in this activity. Evaluation results showed a 75% increase in knowledge and improved behavior regarding personal hygiene and regular physical activity. This activity contributes positively to improving the quality of life among elderly women through promotive and preventive midwifery approaches.